Descriptors for cherimoya (Annona cherimola Mill.) - Bioversity International; Consejo Superior de Investigaciones Cientificas, Spain (Bioversity International, 2008)
The Descriptor list was developed by experts from three Latin American countries (Ecuador, Peru and Bolivia) and three European countries (Spain, Belgium and Austria), partners of the EU-funded project "Promotion of sustainable Cherimoya production systems in Latin America through the characterization, conservation and use of local germplasm diversity".